PENDAFTARAN TANAH UNTUK MEMPEROLEH PERLINDUNGAN HUKUM DAN KEPASTIAN HUKUM DI DESA CIKUNIR - Yanti Haryanti (Jurnal Istimā, 2024)
The issue of land registration in Cikunir Village, Singaparna District, Tasikmalaya Regency, is notably prevalent, making it an ideal location for implementing outreach programmes aimed at promoting legal protection and certainty in land affairs. The Community Service Team (PKM) actively participated in research and volunteer activities, engaging directly with the community to raise awareness of land-related issues. This study aims to analyse and describe the quality of land registration in Cikunir Village and to identify the challenges encountered. The method employed a theoretical approach through a structural framework to evaluate phenomena, including issues in the Complete Systematic Land Registration Programme (PTSL). The findings emphasise the importance of electronic certificates as evidence of land ownership, providing legal certainty and protection. The study draws its legal basis from the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia No. 3 of 2023 on the Issuance of Electronic Documents in Land Registration and Government Regulation No. 18 of 2021 on Land Registration. The results of this study enhance community knowledge and understanding of land law and its challenges, enabling the community to secure legal protection and certainty in land affairs.